Analisis Kelayakan Investasi Mesin Pencetak Bola untuk Memenuhi Kebutuhan Pasar - Abdillah, Nanda Moh Surya; Wati, Putu Eka Dewi Karunia (SURYA TEKNIKA, 2025)
UD. XYZ is facing increasing market demand for striped plastic ball variants but does not yet have a machine capable of producing the product. This study aims to evaluate the feasibility of investing in purchasing a small striped plastic ball molding machine as a strategic solution. A financial feasibility analysis was conducted using the Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (BCR), and Payback Period (PP) methods. The evaluation results indicate that this investment is highly feasible, with a positive NPV of Rp144,594,680, an IRR of 68.48% (exceeding the benchmark interest rate of 10%), and a BCR of 1.295. The payback period is estimated to be only 1 year 5 months 12 days, indicating a fast and efficient return. The implementation of this machine is expected to increase production capacity, meet market demand, and strengthen the company's competitiveness and growth.